Perlindungan Hukum Terhadap Hak-hak Pekerja Harian Lepas Di CV. Indojati Surakarta - Triyono, Aris, Shalman Al-Farizy, SH. M. Kn, Nuswardhani, S.H., MS (2015)
The purpose of this study is to: First, describe the agreements and regulations applicable to non-permanent employees at CV. Indojati Surakarta; Second, analyze the rights and obligations of each party in the employment agreement between CV. Indojati Surakarta with non-permanent employees; Third, analyzing the legal responsibility if one party made a mistake or offense. This research is descriptive research that provides an overview of data as complete on methods or forms of legal protection against non-permanent employees at CV. Indojati Surakarta. This study uses normative legal approach. Data sources using primary data from interviews, observation, and literature study. Data were analyzed using qualitative analysis. The results showed that: First, treaties and regulations applicable to the Daily Worker Lepas International Airport (PHL) at CV. Indojati Surakarta showed that the PHL is not given an employment contract and no written agreement with the company, only in the form of an oral agreement. Work rules applicable to the PHL is the work rules as applicable to permanent workers; Second, the obligation PHL is obliged to carry out the work, obeying the order, pay a fine and compensation in case of damage to the product or equipment caused by worker error, and act as a good worker. PHL rights are earned in accordance with the duties and responsibilities, gain work uniform as much as 1 (one) sets in every 6 (six) months, receive other employment rights, obtain severance if terminated before the work is completed; Third, the mistakes made PHL CV. Indojati Surakarta is resigned prior labor agreement expired. Legal liability to PHL that making mistakes is completing an agreement that is mutually agreed upon, or change the amount of compensation in accordance with the agreement. Keywords: agreements and work rules, rights and obligations of non-permanent employees